2002
DOI: 10.1093/humrep/17.7.1767
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurement of the uterocervical angle before embryo transfer: a prospective controlled study

Abstract: Moulding the embryo transfer catheter according to the uterocervical angle measured by ultrasound increases clinical pregnancy and implantation rates and diminishes the incidence of difficult and bloody transfers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 30 publications
0
50
1
1
Order By: Relevance
“…This helps the gynecologist to choose a suitable catheter for the embryo transfer. It has been reported that the main cause for embryos to fail to arrive at the internal os is that the catheter is not level with the axis of the uterine body and cervical canal (15,18). With the guidance of ultrasound, the catheter can be bent to follow the axis and can easily pass through the cervical canal, which also avoids over-stimulation and injury of the cervix and uterus.…”
Section: Discussionmentioning
confidence: 99%
“…This helps the gynecologist to choose a suitable catheter for the embryo transfer. It has been reported that the main cause for embryos to fail to arrive at the internal os is that the catheter is not level with the axis of the uterine body and cervical canal (15,18). With the guidance of ultrasound, the catheter can be bent to follow the axis and can easily pass through the cervical canal, which also avoids over-stimulation and injury of the cervix and uterus.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantages of this technique compared with standard embryo transfer (performed by clinical feel) include the ability to visualize the uterocervical angle which may aid with difficult transfers, reliably determine the catheter distance from the fundus at the time of embryo transfer, and visualize any unforeseen uterine abnormalities before the transfer. Some studies have demonstrated a benefit in favor of UGET when compared to embryo transfer without ultrasound guidance (Coroleu et al, 2000;Ivanovski et al, 2006;Matorras et al, 2002;Prapas et al, 2001;Sallam et al, 2002;Tang et al, 2001) although others have not (Al-Shawaf et al, 1993;Garcia-Velasco et al, 2002;Kan et al, 1999). Careful examination of the data from four properly randomized clinical trials (Coroleu et al, 2000;Garcia-Velasco et al, 2002;Matorras et al, 2002;Tang et al, 2001) showed a significant advantage to UGET with regard to implantation, clinical pregnancy, and ongoing pregnancy rates (Buckett, 2003;Sallam and Sadek, 2003).…”
Section: Ultrasound and Embryo Transfermentioning
confidence: 99%
“…UTT can theoretically identify those patients with a discrepancy between perceived and actual uterine cavity length in an office setting where logistical issues are of less concern, and thus save UGET for only a select minority of patients where the trial transfer was challenging. The data from their study demonstrate that UTT can be useful method in identifying patients who will otherwise have an inaccurate trial transfer if the procedure were done blindly (Matorras et al, 2002;Sallam et al, 2002). Two studies demonstrated that cavity depth as noted by ultrasound at the time of embryo transfer differed from the cavity depth via office trial transfer by ≥1.0 cm in ≥30% of cases (Pope et al, 2004;Shamonki et al, 2005b).…”
Section: Ultrasound and Embryo Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our experience, published elsewhere 10 , the main advantage of ultrasound guidance of embryo transfer is in facilitating the passage of the embryo-transfer catheter through the uterocervical angle, which is the main site of difficulty during the procedure. This is performed by bending the tip of the catheter according to this angle.…”
mentioning
confidence: 95%